Using the Vitiligo Noticeability Scale in clinical trials: construct validity, interpretability, reliability and acceptability. (1st October 2022) - Batchelor, Jonathan M.; Gran, Sonia; Leighton, Paul; Howells, Laura; Montgomery, Alan A.; Tan, Wei; Ahmed, Isma; Thomas, Kim S.
Abstract: Background: Validated outcome measures are needed for vitiligo trials. Objectives: To assess construct validity, interpretability, reliability and acceptability of the Vitiligo Noticeability Scale (VNS). Methods: We used images of vitiligo before and after treatment, plus outcome data, from the HI‐Light Vitiligo trial. We compared outcome assessments made by trial participants with assessments of images by clinicians and people with vitiligo who were not trial participants [Patient and Public Involvement (PPI) panel]. Hypothesis testing assessed psychometric properties of the VNS, with κ statistics to assess agreement between outcomes. Three focus groups and two online discussion groups provided insight into the use of VNS by people with vitiligo. Results: Our hypothesis of a positive association between VNS and participant‐reported global treatment success was supported for trial participants (κ = 0·41 if VNS success was defined as ≥ 4; κ = 0·71 if VNS success was defined as ≥ 3), but not for the blinded PPI panel (κ = 0·28). As hypothesized, the association with participant‐reported global success was higher for VNS (κ = 0·41) than for clinician‐reported percentage repigmentation (κ = 0·17). Seventy‐five per cent of trial participants valued a VNS of 3 (partial response) as a treatment success. Test–retest reliability was good: κ = 0·69 (95% confidence interval 0·63–0·74). Age and skin phototype did not influence interpretation of the VNS scores. To people with vitiligo, the VNS is an acceptable and meaningful patient‐reported outcome measure. Conclusions: Trial participants may assess their vitiligo differently compared with blinded assessors. A VNS score of 3 may be more highly valued by people undergoing vitiligo treatment than was previously thought. What is already known about this topic?   Vitiligo is a common condition, and can have a considerable psychological impact. A Vitiligo Core Outcome Set is being developed, to enable the results of vitiligo trials to be compared and combined more easily. The Vitiligo Noticeability Scale (VNS) is a patient‐reported outcome measure (PROM) developed in partnership with people with vitiligo; initial validation studies have been promising. What does this study add?   The VNS shows good construct validity, reliability and acceptability; it can be used in all ages and skin phototypes. All five levels of the VNS scale should be reported for transparency, to aid interpretation of trial findings, and to facilitate meta‐analysis in systematic reviews. VNS assessments made by trial participants and independent observers are likely to be qualitatively different, making blinded assessment of VNS by independent observers difficult to interpret. Blinding of participants to trial interventions is recommended whenever possible. What are the clinical implications of the work?   The VNS can be used as a PROM to assess the cosmetic acceptability of repigmentation at individual patches of vitiligo. A VNS score of 3 or more is likely to be valued by patients as a treatment success. Abstract: A Vitiligo Core Outcome Set is being developed, to enable the results of vitiligo trials to be compared and combined more easily The VNS shows good construct validity, reliability and acceptability. It can be used in all ages and skin phototypes The VNS can be used as a PROM to assess cosmetic acceptability of repigmentation at individual patches of vitiligo Linked Comment:  A.G. Pandya and K. Ezzedine. Br J Dermatol 2022; 187:461–462 .